Annual Plan (1999-2000) Andhra Pradesh (Submitted To The Planning Commission) - Planning Commission (Planning Commission, 1999)
Rs.5480 crore is the outlay approved by the Planning Commission for the Annual Plan 1999-2000 which includes Rs. 1848.71 crore for the Externally Aided Projects and Rs.35.75 crore for the National Slum Development Programme (NSDP). The expenditure under the Annual Plan 1998-99 was Rs.4971.97 crore as against the approved outlay of Rs.4681.20 crore. The details of sector-wise outlays under the Annual Plan 1999-2000 are given in Table I&II. The allocations under Special Component Plan, Tribal Sub-plan and Women Component Plan are given in Table-III.
Finance and Planning (Plg.Wing) Department, Government of Andhra Pradesh